Abnormalities of Renal and Lipid Profile in Patients with Thyroid Dysfunction and its Implications - ., ARIF MALIK (Journal of Fatima Jinnah Medical University, 2018)
Background: Lipid and renal profile is markedly influenced by thyroid disorders; however, the relationship among them has not been analyzed in detail in human. Methodology: The blood samples of thirty each hyperthyroid, hypothyroid patientand sex-matched clinically apparently healthy individuals were recruited for the present study. TG, LDL, HDL, total cholesterol, creatinine, urea and uric acid were determined with commercial kits. Results: The results of the present study show that the lipid profile in the patients of hypothyroidism and hyperthyroidism differed significantly. The levels of TCh, TG and LDL were higher (189.45±6.83 mg/dl, 188.67±8.35 mg/dl and 98.27±5.87 mg/dl) in hypothyroid patients as compared to hyperthyroid group (244.39±5.26 mg/dl, 207.52±5.26 mg/dl and 107.56±2.76 mg/dl respectively). Renal profile of hypothyroidism and hyperthyroidism also differed significantly for creatinine, uric acid and urea. Higher levels of urea, uric acid and creatinine were recorded in hypothyroid patients (94.57±2.77 mg/dl, 8.10±0.28 mg/dl and 2.16±0.38mg/dl) in contrast to hyperthyroid group (87.63±1.98 mg/dl, 7.60±0.19 mg/dl and 1.07±0.16 mg/dl respectively) as compared to control. Conclusion: The present study demonstrated that patients with hyperthyroidism had increased levels of TCh and LDL as compared to patients of hypothyroidism. Increased lipid contents remain associated with cardiovascular diseases hence the risk of cardiovascular and renal diseases remain higher in the patients with thyroid disorder.